Evaluation of the use of bamboo as an alternative building material for the construction of social housing - Barboza, Aline da Silva Ramos (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
Bamboo has been recommended as an alternative building material for the construction of social housing, as it presents the same quality as conventional materials and may potentially reduce building costs. However, further studies are needed on its potential uses and limitations. The aim of this study is to assess the use of bamboo in structural and roof elements, and in insulation panels of a low-cost house built in Maceió, Brazil. Technical analysis results and thermal comfort parameters were compared to the users’ perceptions. The study also included a literature review, and the participation of the authors in the construction of house – from bamboo harvesting to actual construction works. A post-occupancy evaluation was carried out through interviews and questionnaires with the user and neighbours. It is suggested that bamboo can be considered as a suitable building material for social housing in Brazil. Most of the negative aspects are related to technical design problems, which can be easily solved applying minor interventions. Positive results, which include the acceptance of this type of building by the user population, require knowledge on care and maintenance, which are unique for this building material.